Across‐species meta‐analysis of dexamethasone pharmacokinetics utilizing allometric and scaling modeling approaches. (17th March 2021) - Song, Dawei; Jusko, William J
Abstract: The pharmacokinetic (PK) parameters of dexamethasone (DEX) in 11 species were collected from the literature and clearances (CL) assessed by basic allometric methods, and concentration–time course profiles were fitted using two PK models incorporating physiological or allometric scaling. Plots of log CL vs. log body weights (BW) correlated reasonably with R 2 = 0.91, with a maximum ratio of actual to fitted CL of 6 (for pig). A minimal physiologically‐based pharmacokinetic (mPBPK) model containing blood and two lumped tissue compartments and integrated utilization of physiological parameters was compared to an allometric two‐compartment model (a2CM). The plasma PK profiles of DEX from 11 species were analyzed jointly, with the mPBPK model having conserved partition coefficients ( K p ), physiologic blood and tissue volumes, and species‐specific CL values. The DEX PK profiles were reasonably captured by the mPBPK model for 9 of 11 species in the joint analysis with three fitted parameters (besides CL) including an overall tissue‐to‐plasma partition coefficient of 1.07. The a2CM with distribution CL and central and peripheral volumes scaled allometrically fitted the plasma concentration profiles similarly but required a total of six parameters (besides CL). Overall, the literature reported that DEX CL values exhibit moderate variability (mean = 0.64 L/h/kg; coefficient of variation = 105%), but distribution parameters were largely conserved across most species. Abstract : Allometric relationship between dexamethasone clearances (intravenous doses) and body weights of 11 indicated species.